Graph transformation : 13th International Conference, ICGT 2020, held as part of STAF 2020, Bergen, Norway, June 25-26, 2020, Proceedings /: 13th International Conference, ICGT 2020, held as part of STAF 2020, Bergen, Norway, June 25-26, 2020, Proceedings. (2020) - Unknown
No abstract available